A Head-To-Head Comparison of Benzbromarone and Allopurinol on the Risk of Type 2 Diabetes Mellitus in People With Asymptomatic Hyperuricemia - Lai, Shih-Wei; Liao, Kuan-Fu; Kuo, Yu-Hung; Lin, Cheng-Li; Liu, Chiu-Shong; Hwang, Bing-Fang (Frontiers in Pharmacology, 2021)
Objective. The study aimed to thoroughly address the influence of benzbromarone and allopurinol on the risk of the development of type 2 diabetes mellitus (T2DM) in people with asymptomatic hyperuricemia. Methods. We conducted an observational cohort study to examine the 2000-2015 national dataset containing all claims data of 23 million beneficiaries in Taiwan. Subjects who already had diabetes mellitus, gout-related diseases, and any cancer prior to the index date were excluded. Asymptomatic hyperuricemia was defined as subjects taking urate-lowering drugs who never had a gout flare. Subjects aged 20-84 with asymptomatic hyperuricemia who had benzbromarone prescriptions were selected as the benzbromarone group. Sex-matched and age-matched subjects with asymptomatic hyperuricemia who had allopurinol prescriptions were identified as the allopurinol group. The maximum follow-up duration was set as 5 years in our study. The outcome was set as subjects who had a new diagnosis of T2DM. The incidence density of T2DM was calculated in the benzbromarone and allopurinol groups. The hazard ratio (HR) and 95% confidence interval (CI) for T2DM was utilized to estimate the correlation between medications and the risk of T2DM. Results. The incidence of T2DM among benzbromarone users was significantly lower than that of allopurinol users (7.91versus 8.48 per 100 person-years, incidence rate ratio=0.93, and 95% CI=0.87-0.99). After adjustment for co-variables, the adjusted HR of T2DM would be 0.91 (95% CI=0.85-0.98 and P=0.008) in benzbromarone users as compared to allopurinol users. Conclusions. There is a small but statistically significant risk reduction of developing T2DM in people with asymptomatic hyperuricemia taking benzbromarone as compared to those taking allopurinol during 5 years of follow-up. It indicates a future research direction for the use of individual urate-lowering drugs on the prevention of T2DM in the general population.